Kinetic, thermodynamic, and ab initio insights of AsnGly isomerisation as a ticking time bomb for protein integrity - Fruzsina Pilhál; Imre Jákli; Ernő Keszei; András Láng; András Perczel (Communications Chemistry)
Abstract Under physiological conditions in peptides or proteins, the -AsnGly- motif autonomously rearranges within hours/days to β-Asp and α-Asp containing sequence, via succinimide intermedier. The formation of the succinimide is the rate-limiting step, with a strong pH and temperature dependence. We found that Arg(+) at the (n + 2) position (relative to Asn in the nth position) favors isomerisation by forming a transition-state like structure, whereas Glu(-) disfavors isomerisation by adopting a β-turn like conformer. Four to six key intermediate structures (proton transfer, transition-state formation, ring-closure and ammonia-release steps) have been identified along the intrinsic reaction coordinate pathways. We explain how, under the right conditions, the N-atom of a backbone amide, hardly a potent nucleophile, can nevertheless initiate isomerisation. The new data are useful for the design of self-structuring motifs, more resistant protein backbones, antibodies, etc.